TANGGUNG JAWAB KUASA PENGGUNA ANGGARAN TERHADAP KEUANGAN NEGARA DALAM PROSES PENGADAAN BARANG/ JASA PEMERINTAH ( STUDI KASUS PENGADAAN ALAT KESEHATAN DI RSU dr. FL. TOBING SIBOLGA - Dearma Sinaga; Pendastaren Tarigan; Faisal Akbar Nasution; Jusmadi Sikumbang (Universitas Sumatera Utara, 2015)
ABSTRACT The goods / services within the government are composed of organizations in the implementation of the Budget User / Authorized Budget, Commitment Officer, Procurement Committee, Managing Committee of Goods, which has the authority duties and responsibilities based positions - each, which is stipulated in President Number 54 Year 2010, the Budget Authority has the duty and authority by delegation of authority from the Budget Users, clearer about the delegation of authority to the Budget Users Budget Authority in Rule Number 1 Head LKPP 2012. Irregularities in the procurement of goods / services can government sanctioned, can be administrative sanctions, penalties and damages State sanction criminal penalties. Keywords: Responsibility, Budget Authority, the State Treasury, Procurement of Goods / Services